Exploring drivers behind university students' aspiration to become social media influencers - Ahmad, Sarah Sabir; Zakaria, Azfahanee; Zainal, Nurdiyana Nazihah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2024)
Social media has become a significant part of daily life. Statista (2021) reports that YouTube has 1.86 billion global users, while Facebook videos attract over 500 million viewers. As social media usage grows, individuals increasingly encounter social media influencers (SMIs). According to Shabahang et al. (2022), SMIs are particularly admired by younger generations, who often aspire to become influencers themselves. An SMI is someone with a large following on social media platforms who can influence their audience’s beliefs, actions, and purchasing decisions. In the realm of influencer marketing, Lou and Yuan (2019) found that SMIs, by producing content in their areas of expertise and targeting a large audience, serve as valuable marketing tools for brands. These influencers often specialize in fashion, beauty, fitness, travel, technology, or lifestyle, leveraging platforms like YouTube and Facebook to reach billions of users. A study by Fetter et al. (2023) reveals that the most common reason for wanting to become an SMI is financial stability. Many people are drawn to social media careers as they seem more lucrative than traditional ones. Becoming an SMI can provide financial motivation through opportunities like paid endorsements, career advancement, and job opportunities (An & Haryanto, 2021). Another common reason is personal branding. In today’s digital environment, social media is the fastest platform to achieve fame and influence, with success often based on establishing a brand identity consumable by audiences and commercial brands. Additionally, the entertainment factor drives young adults to become SMIs, as social media platforms offer intrinsic motivation and amusement (Audrezet et al., 2020). This study investigates the factors driving students' desire to become SMIs at UiTM Kedah. Previous research suggests financial gain is a strong motivator (Bradley, 2022), potentially linked to materialistic values (Shabahang et al., 2022). However, the impact of financial stability on this aspiration remains underexplored. This study aims to bridge this gap. Beyond financial incentives, the strategic use of platforms for personal branding and crafting public personas also attracts potential SMIs (Croes & Bartels, 2021). Concerns about influencers relying on media and advertising for self-promotion and shifting audience relationships highlight the need for further research. Therefore, this study's primary objective is to identify the most significant factors contributing to students' desire to become SMIs, thus 44 shedding light on why this career path is attractive to the younger generation.